Analisis Polisi Luput Pelan Takaful Keluarga - Yaakob, R.; Abdullah, M. H. S. B.; Mohd Baharom, N. (Universiti Sains Islam Malaysia, 2024)
This study aims to analyze the determinants of policy lapse of family's takaful in Malaysia by examining the demographic characteristics of policyholders and the family takaful policy itself. The policy could lapse due to several reasons such as failing to make payment within the prescribed period, converting to a better policy, financial pressure and voluntary surrender. The policy lapse has a huge impact on stakeholders such as takaful operators, customers and policy makers. The impact of policy lapse includes losses to firms, adverse selection, liquidity and contribution increament. The results of the logistic regression analysis show that the sum insured, payment methods and gender have a negative impact on policy lapse. Wheares age, marital status and the insured individual have no effect on policy lapse. The findings assist stakeholders such as takaful operators and regulators to develop appropriate strategies to achieve their goals and support the development of the takaful industry in Malaysia.